When Innate Immunity Meets Angiogenesis—The Role of Toll-Like Receptors in Endothelial Cells and Pulmonary Hypertension - Bhagwani, Aneel; Thompson, A. A. Roger; Farkas, Laszlo (Frontiers in Medicine, 2020)
Toll-like receptors serve a central role in the innate immunity, but they can also modulate cell function in various non-immune cell types including endothelial cells. Endothelial cells are necessary for the organized function of the vascular system, and part of their fundamental role is also the regulation of immune function and inflammation. In this review we summarize the current knowledge of how Toll-like receptors contribute to the immune and non-immune functions of the endothelial cells.